The Readiness Of Private University Graduates In Banten Province To Face The Era Of Artificial Intelligence - Irma Nurmala Dewi; Arta Rusidarma Putra; Hafidz Hanafiah (Proceeding of the International Conference on Global Education and Learning, 2024)
The rapid advancement of artificial Intelligence in education and employment necessitates that universities generate graduates capable of adapting to the future of artificial Intelligence. Numerous studies have examined the adaptation and challenges of implementing AI among students. This study aims to identify the essential values and their incorporation into curricula to enhance students' preparedness for the contemporary workforce influenced by Artificial Intelligence. The study used a qualitative method, using literature studies and empirical studies. The study's findings indicate that students must possess seven skills to effectively compete with advancements in AI technology: problem-solving, critical thinking, creativity and innovation, communication, collaboration, digital data literacy, and ethical judgment. With these skills, students can control and collaborate with technology, making production performance more effective, efficient, and high quality. Acquiring skills to navigate the AI era can be achieved by incorporating Logic, Philosophy, English, Business Management, Research Methodology, Entrepreneurship, and Ethics courses.